Modifications of pulse therapy in pemphigus: a retrospective study of 72 patients - Bhuptani, Neela V.; Chauhan, Khushbu P.; Jadwani, Monal M.; Raja, Pooja (International Journal of Research in Dermatology, 2019)
Background: Pulse therapy defines as the administration of supra-pharmacologic doses of drugs in an intermittent manner to enhance the therapeutic effects and reduce the side effects. Dexamethasone-Cyclophosphamide pulse (DCP) therapy is known since 1986 but there are certain limitations due to side effects of cyclophosphamide. Methods: A retrospective study was carried out where 72 patients of pemphigus were treated with modified pulse therapy like DCP, DAP, DMP from 2006-2016. Modifications were made in DCP therapy protocol and substitution of cyclophosphamide with either azathioprine or methotrexate in few patients. Results: Male to female ratio observed was 1:0.7. Majority of them belonged to age group of 31-40 years (41.66%) followed by 41-50 years (33.3%). Maximum number of patients had pemphigus vulgaris (86.1%) followed by pemphigus foliaceous (12.5%) and IgA pemphigus (1.38%). Good response was observed in patients who took pulse therapy regularly. Conclusions: Modifications to the original DCP therapy protocol were found to be very effective, useful and it shortened the duration of phase I. Side effects were minimal and manageable.